An innovative oral management procedure to reduce postoperative complicationsCentral MessagePerspective - Akari Kaga, DH; Tetsuya Ikeda, DDS, PhD; Keisei Tachibana, MD, PhD; Ryota Tanaka, MD, PhD; Haruhiko Kondo, MD, PhD; Takanori Kawabata, MS; Tomoko Yorozu, MD, PhD; Koichiro Saito, MD, PhD (JTCVS Open, 2022)
Background: Numerous studies have shown that improving oral hygiene contributes to a reduction in the risk of postoperative complications in patients with head and neck cancer, cardiac disease, and esophageal cancer. However, the beneficial standard for oral management procedures during the perioperative period has not yet been established. Therefore, our aim was to determine whether or not their innovative oral management intervention contributed to a reduction in postoperative complications in lung cancer. Methods: We performed a retrospective analysis of medical records of patients who underwent lung cancer surgery with lobectomy and pneumonectomy at Kyorin University Hospital. Patients were divided into 2 groups: a perioperative oral management intervention group that underwent lung cancer surgery from April 2016 to March 2018 (n = 164), and a control group without oral management that underwent surgery from April 2014 to March 2016 (n = 199). In particular, our oral management procedure emphasized oral mucosa stimulation to induce saliva discharge as in gum chewing, rather than simply using teeth brushing to reduce oral microbiome. Therefore, our oral management procedure is different from traditional oral care. Results: This study demonstrated that our oral management practice was associated with a decline in the occurrence of postoperative pneumonia (odds ratio, 0.184; 95% CI, 0.042-0.571; P = .009), postoperative hospital stay duration (β coefficient, −4.272; 95% CI, −6.390 to −2.155; P < .001) and Clavian-Dindo classification grade II or above (odds ratio, 0.503; 95% CI, 0.298-0.835; P = .009). Conclusions: We propose an innovative new strategy using their unique oral management procedure to reduce postoperative complications resulting from pulmonary resection.